2010
DOI: 10.1007/s10533-010-9473-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patterns in pH and colour in small acidic boreal lakes of varying hydrological and landscape settings

Abstract: Changes in water pH and colour since the late 1980s were studied in 35 small boreal lakes of varying hydrological and landscape settings but similar climate and acid deposition. The data was collected during the autumnal overturn on the annual basis except in lake with weekly sampling during the ice-free period. In addition to the deposition data information about catchment soil types as well as local meteorological and hydrological conditions were used for the long-term data interpretation. The lakes are situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…It is also a critical factor when natural water is purified to produce good-quality water for domestic and industrial purposes (Chow et al, 2007). During the past two decades over the northern hemisphere, color has increased along with the concentration of iron (Fe) and total organic carbon (TOC) (Roulet and Moore, 2006;Arvola et al, 2010;Haaland et al, 2010;Kritzberg and Ekström, 2012;Köhler et al, 2013;Sarkkola et al, 2013;Weyhenmeyer et al, 2014). The organic chromophores of TOC (referred to here as colored organic carbon, COC; see Table 1 for acronyms used; Coble, 2007;Fichot and Benner, 2011;Carter et al, 2012) and chromophores of Fe (Shapiro, 1964;Kritzberg and Ekström, 2012;Xiao et al, 2013) are important sources of color (Weyhenmeyer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is also a critical factor when natural water is purified to produce good-quality water for domestic and industrial purposes (Chow et al, 2007). During the past two decades over the northern hemisphere, color has increased along with the concentration of iron (Fe) and total organic carbon (TOC) (Roulet and Moore, 2006;Arvola et al, 2010;Haaland et al, 2010;Kritzberg and Ekström, 2012;Köhler et al, 2013;Sarkkola et al, 2013;Weyhenmeyer et al, 2014). The organic chromophores of TOC (referred to here as colored organic carbon, COC; see Table 1 for acronyms used; Coble, 2007;Fichot and Benner, 2011;Carter et al, 2012) and chromophores of Fe (Shapiro, 1964;Kritzberg and Ekström, 2012;Xiao et al, 2013) are important sources of color (Weyhenmeyer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the world's surface waters are becoming less transparent as a result of increased inputs of DOC from the watershed and recovery from acidification (Forsberg 1992, Gunn et al 2001, Arvola et al 2010. Evans et al (2006) showed DOC concentration of lakes in the United Kingdom has increased by 63% between the periods of 1988-1993-2003.…”
Section: Introductionmentioning
confidence: 99%
“…Because of increased runoff the lakes received high load of inorganic nutrients and organic matter from their catchment areas [28,31]. Therefore, epilimnetic DOC, colour, TP, TN, NO 3 , NH 4 and Fe concentrations increased 2-to 4-fold until the middle of August compared to the early June [21]. As a result of the increase in colour and DOC, light penetration into the lake radically diminished.…”
Section: General Aspects Of Samplingmentioning
confidence: 99%
“…Seasonal and inter-annual changes in the weather therefore have a major impact on the thermal characteristics of lakes. However, lakes with contrasting morphometry may respond differently to changes in weather [3,4]. For example, deep lakes with large water volume integrate the effects of meteorological forcing over longer time periods than shallow lakes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation